Reviewing bryophyte-microorganism association: insights into environmental optimization - Dangar, Bhagyashri V.; Chavada, Pratikkumar; Bhatt, P. J.; Raviya, Rajesh (Frontiers in Microbiology, 2024)
Bryophytes, the second-largest group of plants, play a crucial role as early colonizers of land and are a prolific source of naturally occurring substances with significant economic potential. Microorganisms, particularly bacteria, cyanobacteria, fungi form intricate associations with plants, notably bryophytes, contributing to the ecological functioning of terrestrial ecosystems and sometimes it gives negative impact also. This review elucidates the pivotal role of endophytic bacteria in promoting plant growth, facilitating nutrient cycling, and enhancing environmental health. It comprehensively explores the diversity and ecological significance of fungal and bacterial endophytes across various ecosystems. Furthermore, it highlights the moss nitrogen dynamics observed in select moss species. Throughout the review, emphasis is placed on the symbiotic interdependence between bryophytes and microorganisms, offering foundational insights for future research endeavors. By shedding light on the intricate bryophyte-microorganism associations, this study advances our understanding of the complex interplay between plants, microbes, and their environment, paving the way for further research and applications in environmental and biotechnological realms.